Preliminary research on environmental literacy and conservation toward eco-tourism through the community learning centre - Budiyono Saputro; Fadhil Ardhiansyah (Sustinere: Journal of Environment and Sustainability, 2018)
Coastal abrasion has caused the destruction of the mangrove forest in Mojo Pemalang Village. Thus, a preliminary study of communities’ literacy about conservation at Mojo Village, Pemalang, was required to develop the potential of mangrove forest ecotourism. This study aimed to understand the fishermen’s literacy about conservation at Mojo Village, Pemalang related with the development of mangrove forest ecotourism through the Community Learning Center (CLC). The type of research was qualitative descriptive. The research subjects were fishermen in Mojo Village, Pemalang, Central Java, Indonesia. The results of a preliminary study of six indicators of environmental literacy and conservation developed by the North American Association for Environmental Education (2011) and Rush et al. (1999) are as follows: ecological knowledge = 6.02%, verbal commitment = 6.02%, environmental sensitivity = 6.02%, identification = 12.04%, issue analysis = 6.02%, and real commitment = 6.02%. The overall percentage was 42.14% and was included in the low category. The results of the preliminary study indicated that Mojo fishing communities’ literacy about conservation of the environment towards mangrove forests still needed to be improved. A solution suggested based o the results of a preliminary study was the implementation of mangrove ecotourism Community Learning Center (CLC), conducted through several pieces of training, including conservation training, education training, tourism training, and economic training.